(untitled) (Comparative & International Education Series, 2022)
“What do you call someone who speaks two languages? Bilingual. What do you call someone who speaks three languages? Trilingual. Okay. What do you call someone who speaks one language? An American.” This joke has been told to me in multiple countries. It is a poignant reminder to Americans that the United States is not an island, and that second-world language abilities matter. I learned experientially of the complexity of language as a U.S. student on a Fulbright fellowship in Morocco in 2010-2011. Morocco was the perfect place to learn some Korean, Japanese, French, Amazigh, Moroccan Arabic, Modern Standard, and Classical Arabic.